1995
DOI: 10.1002/polb.1995.090331713
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dielectric relaxations associated with the glass transition of vinylidene fluoride and trifluoroethylene copolymers by thermally stimulated current

Abstract: Thermostimulated current (TSC) spectroscopy was applied to the characterization of dielectric relaxations associated with the glass transition of a series of P(VDF/TrFE) copolymers. The maximum temperature of the β‐mode increases slightly as the TrFE unit content is increased, in the same manner as the glass transition temperature. By using the technique of fractional polarizations to the resolution of this relaxation mode, we have isolated, for all the polymers investigated, a series of elementary relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Both these interpretations seem rather vague in terms of molecular origin for the γ‐mode because the involved relaxing entities are not defined nor located. The main β‐mode corresponds to the dielectric manifestation of the glass transition, related to micro‐Brownian motions within the amorphous phase …”
Section: Resultsmentioning
confidence: 99%
“…Both these interpretations seem rather vague in terms of molecular origin for the γ‐mode because the involved relaxing entities are not defined nor located. The main β‐mode corresponds to the dielectric manifestation of the glass transition, related to micro‐Brownian motions within the amorphous phase …”
Section: Resultsmentioning
confidence: 99%
“…29,34,45,46,49,74,83,104,119,128,129,140 It was found by Sasabe et al 107 that PVDF shows three relaxations. In the TSC measurements, the α a -relaxation at around −30 ○ C corresponds to the glass transition and is attributed to the micro-Brownian motion of the amorphous phase, the α c -relaxation is assigned to molecular motions in the crystalline regions of α-PVDF and is found at 80 ○ C. At temperatures of around −50 ○ C and at frequencies between 100 Hz and 1 kHz the dielectric spectra reveal the β-relaxation attributed to local motions within the frozen main chains in the amorphous regions.…”
Section: Effect Of Stable Ferroelectric Polarization On Thermally Stimentioning
confidence: 97%
“…As the temperature increases the β-relaxaion becomes indistinguishable from the α a -relaxation in the dielectric spectra. 107 7 TSC and DSC measurements of P(VDF-TrFE) with different molar fractions, performed by Teyssedre et al, [128][129][130] showed two relaxations which refer to the glas transition between −50 ○ C and −30 ○ C as well as a relaxation associated to crystallites between 20 ○ C and 50 ○ C. Referring to Teyssedre et al 129,130 this temperature however would only be related to crystal domains in so far as it has been ascribed to reorganizations at the crystallites surface rather than in the bulk of crystallites. Another explanation concerning the relaxation between 20 ○ C and 50 ○ C has been but forward by Rollik et al, 105 who studied stretched PVDF films by means of different poling schemes.…”
Section: Effect Of Stable Ferroelectric Polarization On Thermally Stimentioning
confidence: 99%
“…This behavior confirms that the increase in the dielectric permittivity is due to the b dielectric relaxation in PVDF. 28 Dielectric relaxation strength is the difference between the dielectric permittivity before and after the relaxation; a dielectric relaxation strength of 51 is seen in 0.5 wt. % PR-GO-PVDF compared to 4 for unmodified PVDF at 20 Hz as shown in Fig.…”
Section: Electrical Propertiesmentioning
confidence: 99%